Effects of model reuse support in qualitative simulation. (1st January 2012) - Matsuo, Tokuro
In this paper, we propose a unified modelling set of components used in all sorts of graph-based simulations. The set of components consists of qualitative conditions and values of nodes, transmission of effects, relationships of static rule and several others. When a simulation model is developed and given the condition/assumption of nodes and arcs in actual use of simulator, the model is completed by referring from our defined set of components. Further, we propose a method and support to make a graph model based on tree-structured chart and a reuse method of subgraph in the simulation graph model. As advantage of out methods, even though the object of simulation cannot be described by the qualitative differential equation, the simulation model is defined by using the graph-based simulation model. Further, graph can also be checked whether there are errors by oversight or not.